LITERARY RESPONSES TO THE BRITISH EMPIRE: POSTCOLONIAL READINGS OF 20TH CENTURY ENGLISH FICTION - P L, Mylaraiah (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Here shown to be inextricably bound up with the new forms of identity, power and resistance which developed within British imperial culture by examining a total range of 20th-century English fiction. Through a reading of canonical texts like E.M. Forster’s A Passage to India, Joseph Conrad's Heart of Darkness and Jean Rhys' Wide Sargasso Sea the paper comes in terms with how these books critique the imperialist/colonial ideologies. The analysis sheds light on the longstanding literary function of English fiction for imperialist narratives as well as subversive and critical potential. Key themes under consideration are the depiction of cultural identity, hybridity in postcolonial subjects and forms of resistance adopted by characters featured within these ‘narratives. It also introduces the persistence of imperial thematic in English literature even after the official decline of British Empire and discusses how decolonization influenced (or not) literary themes and narratives. This work shows that postcolonial theory is still new and dynamic within the field of literary criticism, offering potential paths for future research into how this theme has developed in modernity and international settings.